Systematic Mapping of the Harmonization of SCRUM and ISO 9001 - Burbano-Delgado, Darly-Liliana; Pardo-Calvache, César-Jesús; Orozco-Garcés, Carlos-Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Small and medium-sized companies have limitations related to the amount of human talent and capital they have, which causes their processes to be disorganized and affects the quality of the products or services they offer. To address this problem, several solutions that allow companies to improve their processes and the way their projects are managed have appeared, some of the most common in the software industry are Scrum and the ISO 9001 standard or its Latin American variants (NTC 6001, NTG 66006 and NTE INEN 2537). In this sense, the objective of this article is to present the results obtained after carrying out a systematic mapping of the literature to identify proposals and related studies. Although it was possible to identify some related studies, the topic has great relevance for the software industry given the benefits that would be enabled in an integrated manner by implementing a quality management system based on the specifications of the ISO standard together with the agile approach Scrum. In conclusion, it was possible to observe that, although there are differences between the ISO and Scrum standards, they are not incompatible, on the contrary, they turn out to be complementary.